Dried blood spot-based free sterol signatures in sitosterolemia diagnostics - Kwon, Go Eun; Son, Hyun-Hwa; Moon, Ju-Yeon; Lee, Ayoung; Jung, Mo Kyung; Rhie, Seonkyeong; Park, Mi Jung; Garg, Abhimanyu; Yoo, Eun-Gyong; Choi, Man Ho (Elsevier BV, 2024)
Background: Sitosterolemia is a rare inherited lipid metabolic disorder characterized by increased levels of plant sterols and accelerated atherosclerosis. Although early detection is beneficial for the prevention of disease progression, it is largely underdiagnosed by routine screening based on conventional lipid profiles. Materials and methods: A gas chromatography-mass spectrometry (GC-MS)-based profiling has been developed and validated to measure the levels of biologically active free sterols, including five endogenous sterols and three plant sterols (sitosterol, campesterol, and stigmasterol) in dried blood spot (DBS). Results: Within- and between-run precisions were 1.4-11.1 % and 2.2-14.1 %, respectively, while the accuracies were all 86.3 similar to 121.9 % with the correlation coefficients (r(2)) > 0.988 for all the sterols. In the patients (four girls and two boys, 6.5 +/- 2.8 years), sitosterol levels were significantly increased, with an optimal cut-off value of 2.5 mu g/mL distinguishing them from ninety-three age-matched healthy children. A cut-off value of 31.9 mu g/mL differentiated the patients from six ABCG5/ABCG8 heterozygous carriers. In addition, the molecular ratios of sitosterol to cholesterol, desmosterol, and 7-dehydrocholesterol provided excellent cut-off values of 26.3, 67.6, and 21.6, respectively, to distinguish patients from both healthy controls and heterozygous carriers. Conclusions: The novel DBS-based GC-MS profiling of free sterols accurately identified patients with sitosterolemia, with a performance comparable to that of a serum assay. The DBS profiling could be more feasible method in clinical practice as well as population screening programs, and it can provide diagnostic cut-off values for individual plant sterols.